Irisin protects against cerebral ischemia reperfusion injury in a SIRT3-dependent manner - Cong, Yushuang; Guo, Ruichun; Li, Chenglong; Li, Qi; Qi, Sihua (Frontiers in Pharmacology, 2025)
BackgroundCerebral ischemia-reperfusion (CIR) injury critically impacts stroke prognosis, yet effective therapeutic strategies remain limited. Irisin, an exercise-induced myokine, exhibits neuroprotective effects against cerebral ischemia. SIRT3, a mitochondrial deacetylase, is similarly implicated in mitigating ischemia-reperfusion injury. Given that irisin exerts protection via AMPK/PGC-1α pathway activation and SIRT3 acts downstream of PGC-1α , we hypothesized that SIRT3 mediates irisin's neuroprotection in CIR injury.MethodsIn vivo cerebral ischemia-reperfusion injury was modeled by inducing transient middle cerebral artery occlusion (MCAO) in mice, while in vitro CIR conditions were replicated using oxygen-glucose deprivation (OGD) in PC12 neuronal cultures. To elucidate the mechanistic role of SIRT3, targeted interventions were implemented: SIRT3 expression was silenced via transfection with small interfering RNA (siRNA), and its enzymatic activity was pharmacologically inhibited using 3-TYP, a selective SIRT3 inhibitor. Apoptotic were systematically evaluated through TUNEL staining, Western blot analysis of caspase-3, Bax and Bcl-2. Oxidative stress parameters, including malondialdehyde (MDA) levels and glutathione (GSH) content, were measured using colorimetric assays. Neurological function in mice was quantified using the modified Neurological Severity Score (mNSS).ResultsOur results demonstrated that irisin mitigates apoptosis and oxidative stress by dose-dependently activating SIRT3 signaling. At the optimal dosage, irisin effectively restored SIRT3 expression levels, reduced neuronal damage, and improved neurological recovery in CIR injury models. Notably, the therapeutic effects of irisin were significantly attenuated by 3-TYP, a specific SIRT3 inhibitor. Further validation through in vitro experiments revealed that SIRT3 overexpression synergistically enhanced irisin-mediated protection against OGD-induced injury, whereas SIRT3 knockout substantially diminished its efficacy.ConclusionOur data shown that irisin exerted a protective role in CIR injury, at least in part, through SIRT3 activation. This study establishes the irisin/SIRT3 as a novel therapeutic target for ischemic stroke, providing mechanistic insights for future interventions.